Specific absorption rate implications of within‐scan patient head motion for ultra‐high field MRI. Issue 5 (17th April 2020) - Kopanoglu, Emre; Deniz, Cem M.; Erturk, M. Arcan; Wise, Richard G.
Abstract : Purpose: This study investigates the implications of all degrees of freedom of within‐scan patient head motion on patient safety. Methods: Electromagnetic simulations were performed by displacing and/or rotating a virtual body model inside an 8‐channel transmit array to simulate 6 degrees of freedom of motion. Rotations of up to 20° and displacements of up to 20 mm including off‐axis axial/coronal translations were investigated, yielding 104 head positions. Quadrature excitation, RF shimming, and multi‐spoke parallel‐transmit excitation pulses were designed for axial slice‐selection at 7T, for seven slices across the head. Variation of whole‐head specific absorption rate (SAR) and 10‐g averaged local SAR of the designed pulses, as well as the change in the maximum eigenvalue (worst‐case pulse) were investigated by comparing off‐center positions to the central position. Results: In their respective worst‐cases, patient motion increased the eigenvalue‐based local SAR by 42%, whole‐head SAR by 60%, and the 10‐g averaged local SAR by 210%. Local SAR was observed to be more sensitive to displacements along right–left and anterior–posterior directions than displacement in the superior–inferior direction and rotation. Conclusion: This is the first study to investigate the effect of all 6 degrees of freedom of motion on safety of practical pulses. Although the results agree with the literature for overlapping cases, the results demonstrate higher increases (up to 3.1‐fold) in local SAR for off‐axis displacement in the axial plane, which had received less attention in the literature. This increase in local SAR could potentially affect the local SAR compliance of subjects, unless realistic within‐scan patient motion is taken into account during pulse design.